Two new species of the genus Irepacma Moriuti, Saito & Lewvanich (Lepidoptera: Oecophoridae) from Guizhou Province, China - Wang, Jing-Jing; Wang, Shu-Xia (Zootaxa, 2011)
Irepacma was established by Moriuti, Saito & Lewvanich in 1985, with Irepacma pakiensis Moriuti, Saito & Lewvanich, 1985 as the type species. It shared the two-segmented labial palpus in male with the closely related genera Periacma Meyrick, 1894, Ripeacma Moriuti, Saito & Lewvanich, 1985 and Epiracma Wang, 2005. The typical character to distinguish Irepacma from its allies is the absence of the apophyses anteriores in the female genitalia. In the male genitalia it is closer to Periacma Meyrick, but can be distinguished mostly by the absence of the dorso-proximal process of the valva, or by having a dorso-proximal process that often far exceeds half the length of the valva.